(untitled) (Research, Society and Development, 2021)
The aim of this work was to evaluate the perception of students from a Nutrition Course at a Public University in Brazil to the Emergency Remote Teaching. A cross-sectional study was carried out in two moments, at the beginning and after implementation of the Emergency Remote Teaching, considering the students according to the University access system, through public policies of Affirmative Actions (AA) or Broad Competition (BC). Initially, 159 entries per AA and 192, per BC, via Google Forms participated, in order to understand the difficulties and facilities in relation to the implementation of the Emergency Remote Teaching. In the second moment, an attitudinal electronic form of the Likert type was applied, covering pedagogical aspects and study environment. The comparison between the scores of the AA and BC students was performed using Student’s t test. Likert-type items were presented as medians and interquartile ranges, and categorical variables, expressed as absolute and relative frequencies. The association between categorical variables was verified by the chi-square test of independence. The significance level was 5%. AA individuals had significant difficulties in accessing, signal and equipment quality, and also presented poorer quality of the study environment at home. With institutional help, the students judged that the Emergency Remote Teaching was necessary and met the educational requirements arising from the pandemic in the first semester of implementation. Continuing Emergency Remote Teaching will require, on the part of the management of Academic Units, monitoring of academic aspects and resolution of difficulties with other instances involved with higher education.